Menganalisis Trapis Dalam Pembinaan Anak Berkebutuhan Khusus Pada Hambatan Penglihatan, Pendengaran dan Komunikasi - Yunanda Putri Panjaitan (Asesment : Journal Of Counseling Guidance, 2023)
This research analyzes the trappings of coaching Children with Special Needs on Vision, Hearing, and Communication Barriers. The subject of this research is children with special needs who have vision, hearing, and communication barriers. The research method used is the Literature review method. The literature review method is a form of research by searching existing research and literature. Research was carried out by reviewing the literature to obtain references appropriate to the research topic. The data sources used as material for this research are books, journals, and internet sites related to the chosen topic. The analysis of this research concludes that the ideal traps to use are the sand playing traps to improve motor skills for children with special needs who are visually impaired and the traps as a video visual learning medium for children with special needs who are hearing impaired.